Hubungan Antara Beban Kerja dengan Stres Kerja Perawat di Ruang Rawat Inap RSI Sultan Agung Semarang - Asti Septania; Dyah Wiji Puspita Sari; Retno Issroviatiningrum (Protein : Jurnal Ilmu Keperawatan dan Kebidanan., 2025)
Excessive workload can cause work stress among nurses, impacting their performance and the quality of healthcare services. Nurses in inpatient wards often experience this due to high job demands and a large number of patients. This study aims to analyze the relationship between workload and work stress levels among nurses in the inpatient ward of RSI Sultan Agung Semarang. This quantitative research employed a correlational design. A total of 100 nurses from the inpatient ward of RSI Sultan Agung Semarang were selected using total sampling. Data were obtained from a questionnaire measuring physical and psychological workload aspects and work stress indicators such as emotional exhaustion and decreased personal accomplishment. Data were analyzed using the Chi-Square test. The majority of respondents (82.8%) had a moderate workload, while most (76.8%) experienced moderate work stress. Bivariate analysis indicated a significant relationship between workload and work stress levels (< 0.05). A high workload significantly contributes to boost work stress levels among nurses in the inpatient ward of RSI Sultan Agung Semarang. Effective workload management strategies, such as adjusting nurse-to-patient ratios and providing stress management programs, are necessary to improve nurse well-being and enhance the quality of healthcare services